EPIDEMIOLOGY OF THERAPY-RELATED MYELOID NEOPLASMS IN THE NORDIC COUNTRIES - Kjeld Schmiegelow (Mediterranean Journal of Hematology and Infectious Diseases)
<p class="MsoBodyText" style="mso-hyphenate: none; tab-stops: -42.5pt 0cm 42.5pt 3.0cm 127.6pt 170.15pt 212.7pt 255.2pt 297.75pt 340.3pt 382.85pt 425.4pt 467.9pt 510.45pt 553.0pt 595.55pt 638.1pt 680.6pt 723.15pt;">Of 1614 Nordic children with ALL that were treated according to the NOPHO ALL92 protocol, 20 developed an SMN (cumulative risk at 12 years: 1.6%). Sixteen of the twenty SMNs were acute myeloid leukemias or myelodysplasias, and 9 of these had either monosomy 7 (n=7) or 7q deletions (n=2). In Cox multivariate analysis longer duration of oral MTX/6MP maintenance therapy (p=0.02; being longest for standard risk patients) and presence of high-hyperdiploidy (p=0.07) were related to an increased risk of SMN. In 524 patients we determined the erythrocyte activity of thiopurine methyltransferase (TPMT), which methylates 6MP and its metabolites, and thus reduces cellular levels of cytotoxic 6-thioguanine nucleotides. The TPMT activity was significantly lower in those that did compared to those that did not develop an SMN (Median: 12.1 vs 18.1 IU/ml; p=0.02). Among 427 TPMT wild type patients, those who developed SMN received higher 6MP doses than the remaining (69.7 vs 60.4 mg/m2, p=0.03), which may reflect increased levels of methylated metabolites that inhibit purine de novo synthesis and thus enhance incorporation of 6-thioguanine nucleotides into DNA. In conclusion, the duration and intensity of 6MP/MTX maintenance therapy of childhood ALL may influence the risk of SMN. <p class="MsoBodyText" style="mso-hyphenate: none; tab-stops: -42.5pt 0cm 42.5pt 3.0cm 127.6pt 170.15pt 212.7pt 255.2pt 297.75pt 340.3pt 382.85pt 425.4pt 467.9pt 510.45pt 553.0pt 595.55pt 638.1pt 680.6pt 723.15pt;">